Intracranial complications of transorbital stab wounds. - De Villiers, J C (1975)
Oscular and orbital injuries due to stab wounds may mask underlying serious intracranial damage. The correct clinical assessment and treatment of such cases require the attention of a team comprising a neurosurgeon, ophthalmologist, otolaryngologist, and plastic surgeon.